Exploring the Learning Barriers in Mathematics for Hearing-Impaired Students in Inclusive Classrooms - Akmal Tsaqifiya Salma (Universitas Sebelas Maret, 2025)
This study aims to identify the barriers and difficulties encountered by students with hearing impairments in learning mathematics in an inclusive classroom. This research employed a descriptive qualitative approach, involving students from SMP Negeri 2 Sewon, Bantul, and the inclusive class teacher as research subjects. Research instruments in the form of interviews and observations were used to collect data on the learning challenges faced by students with hearing impairments. Data analysis was conducted through data reduction, which involved filtering important information obtained from interviews and observations. The reduced data was then presented in a narrative form before drawing conclusions. The results indicate that the inclusive classroom setting provides both opportunities and challenges for students with hearing impairments, who often face difficulties in understanding mathematical concepts due to limitations in verbal communication and insufficient instructional strategies. Teachers reported the necessity of using clear lip movements and personalized teaching strategies, such as cooperative learning and differentiated instruction, to bridge these gaps. Additionally, the inclusive classroom fosters empathy and collaborative skills among all students, while the assessment standards for students with hearing impairments are adapted to align with their unique needs and abilities. This study is expected to provide a deep understanding of the barriers faced by students with hearing impairments in learning mathematics in an inclusive classroom.